Membrane-anchored serine protease matriptase regulates epithelial barrier formation and permeability in the intestine - Buzza, Marguerite S. (National Academy of Sciences, 2010)
The intestinal epithelium serves as a major protective barrier between the mammalian host and the external environment. Here we show that the transmembrane serine protease matriptase plays a pivotol role in the formation and integrity of the intestinal epithelial barrier. St14 hypomorphic mice, which have a 100-fold reduction in intestinal matriptase mRNA levels, display a 35% reduction in intestinal transepithelial electrical resistance (TEER). Matriptase is expressed during intestinal epithelial differentiation and colocalizes with E-cadherin to apical junctional complexes (AJC) in differentiated polarized Caco-2 monolayers. Inhibition of matriptase activity using a specific peptide inhibitor or by knockdown of matriptase by siRNA disrupts the development of TEER in barrier-forming Caco-2 monolayers and increases paracellular permeability to macromolecular FITC-dextran. Loss of matriptase was associated with enhanced expression and incorporation of the permeability-associated, “leaky” tight junction protein claudin-2 at intercellular junctions. Knockdown of claudin-2 enhanced the development of TEER in matriptase-silenced Caco-2 monolayers, suggesting that the reduced barrier integrity was caused, at least in part, by an inability to regulate claudin-2 expression and incorporation into junctions. We find that matriptase enhances the rate of claudin-2 protein turnover, and that this is mediated indirectly through an atypical PKCζ-dependent signaling pathway. These results support a key role for matriptase in regulating intestinal epithelial barrier competence, and suggest an intriguing link between pericellular serine protease activity and tight junction assembly in polarized epithelia.